Changes of White Matter Diffusion Anisotropy in Response to a 6-Week iPad Application-Based Occupational Therapy Intervention in Children with Surgically Treated Hydrocephalus: A Pilot Study - Yuan, Weihong; Harpster, Karen; Jones, Blaise V.; Shimony, Joshua S.; McKinstry, Robert C.; Weckherlin, Nicole; Powell, Stephanie S.; Barnard, Holly; Engsberg, Jack; Kadis, Darren S.; Dodd, Jonathan; Altaye, Mekibib; Limbrick, David D.; Holland, Scott K.; Simpson, Sarah M.; Bidwell, Sarah; Mangano, Francesco T. (Neuropediatrics, 2016)
Objective Our aims were (1) to test whether diffusion tensor imaging (DTI) could detect underlying white matter (WM) changes after a 6-week iPad application-based occupational therapy (OT) intervention in children with surgically treated hydrocephalus (HCP); and (2) to explore the association between WM changes and performance outcomes.Methods Five children (age range: 6.05–9.10 years) with surgically treated HCP completed an intensive iPad-based OT intervention targeting common domains of long-term deficits in children with HCP. The intervention included 6 weekly sessions in an OT clinic supplementing home-based program (1 hour/day, 4 days/week). DTI and neuropsychological assessments were performed before and after the intervention.Observation After the therapy, significant increases in fractional anisotropy (FA) and/or decreases in radial diffusivity were found in extensive WM areas. All participants demonstrated an increased perceptual reasoning index (PRI, Wechsler Abbreviated Scale of Intelligence: 2nd edition, PRI gains = 14.20 ± 7.56, p = 0.014). A significant positive correlation was found between PRI increase and the increase of FA in the right posterior limb of the internal capsule and the right external capsule (both p < 0.05).Conclusion This study provides initial evidence of DTI's sensitivity to detect subtle WM changes associated with performance improvements in response to a 6-week OT intervention in children with HCP.
Keywords: DTI; iPad application; occupational therapy; pediatric hydrocephalus